Seamless integration of MANET and the internet with terminal mobility supported by SIP. (25th May 2012) - Wongsaardsakul, Thirapon; Kanchanasut, Kanchana
To provide seamless real–time multimedia communications between Mobile Ad Hoc Networks (MANETs) and the internet, we adopt the Session Initiation Protocol (SIP) to handle terminal mobility. MANETs can be frequently disrupted, thus a P2P SIP is introduced over an overlay network on MANET, called Structured Mesh Overlay Network (SMON). To connect to the internet, we stretch SMON on MANET to include SMON on the internet and apply P2P SIP on top of this extended SMON, or SMON+. Handoff delays of our proposed scheme were compared with mobile–IP based network mobility approach, or MANEMO. It was found that the mid–call mobility handoff delay of P2P SIP on SMON+ were signicantly lower than that of MANEMO.